Effect of Cavity Cleanser With Long-Term Antibacterial and Anti-Proteolytic Activities on Resin–Dentin Bond Stability - Yaping Gou (Frontiers Media S.A., 2021)
ObjectiveSecondary caries caused by oral microbiome dysbiosis and hybrid layer degradation are two important contributors to the poor resin–dentin bond durability. Cavity cleansers with long-term antimicrobial and anti-proteolytic activities are in demand for eliminating bacteria-induced secondary caries and preventing hybrid layers from degradation. The objectives of the present study were to examine the long-term antimicrobial effect and anti-proteolytic potential of poly(amidoamine) dendrimers with amino terminal groups (PAMAM-NH2) cavity cleanser.MethodsAdsorption tests by attenuated total reflectance–infrared (ATR-IR) spectroscopy and confocal laser scanning microscopy (CLSM) were first performed to evaluate whether the PAMAM-NH2 cavity cleanser had binding capacity to dentin surface to fulfill its relatively long-term antimicrobial and anti-proteolytic effects. For antibacterial testing, Streptococcus mutans, Actinomyces naeslundii, and Enterococcus faecalis were grown on dentin surfaces, prior to the application of cavity cleanser. Colony-forming unit (CFU) counts and live/dead bacterial staining were performed to assess antibacterial effects. Gelatinolytic activity within the hybrid layers was directly detected by in situ zymography. Adhesive permeability of bonded interface and microtensile bond strength were employed to assess whether the PAMAM-NH2 cavity cleanser adversely affected resin–dentin bonding. Finally, the cytotoxicity of PAMAM-NH2 was evaluated by the Cell Counting Kit-8 (CCK-8) assay.ResultsAdsorption tests demonstrated that the binding capacity of PAMAM-NH2 on dentin surface was much stronger than that of 2% chlorhexidine (CHX) because its binding was strong enough to resist phosphate-buffered saline (PBS) washing. Antibacterial testing indicated that PAMAM-NH2 significantly inhibited bacteria grown on the dentin discs as compared with the control group (p < 0.05), which was comparable with the antibacterial activity of 2% CHX (p > 0.05). Hybrid layers conditioned with PAMAM-NH2 showed significant decrease in gelatin activity as compared with the control group. Furthermore, PAMAM-NH2 pretreatment did not adversely affect resin–dentin bonding because it did not decrease adhesive permeability and microtensile strength. CCK-8 assay showed that PAMAM-NH2 had low cytotoxicity on human dental pulp cells (HDPCs) and L929.ConclusionsPAMAM-NH2 cavity cleanser developed in this study could provide simultaneous long-term antimicrobial and anti-proteolytic activities for eliminating secondary caries that result from a dysbiosis in the oral microbiome and for preventing hybrid layers from degradation due to its good binding capacity to dentin collagen matrix, which are crucial for the maintenance of resin–dentin bond durability.